Why Do Disordered and Structured Proteins Behave Differently in Phase Separation?. Issue 7 (July 2018) - Zhou, Huan-Xiang; Nguemaha, Valery; Mazarakos, Konstantinos; Qin, Sanbo
Abstract : Intracellular membraneless organelles and their myriad cellular functions have garnered tremendous recent interest. It is becoming well accepted that they form via liquid–liquid phase separation (LLPS) of protein mixtures (often including RNA), where the organelles correspond to a protein-rich droplet phase coexisting with a protein-poor bulk phase. The major protein components contain disordered regions and often also RNA-binding domains, and the disordered fragments on their own easily undergo LLPS. By contrast, LLPS for structured proteins has been observed infrequently. The contrasting phase behaviors can be explained by modeling disordered and structured proteins, respectively, as polymers and colloids. These physical models also provide a better understanding of the regulation of droplet formation by cellular signals and its dysregulation leading to diseases. Highlights: Phase separation leading to protein droplets and membraneless organelles (MLOs) is determined by the balance between translational entropy of protein molecules and steric and attractive interactions between molecules. Colloids and polymers serve as good models for understanding the different phase behaviors of structured and disordered proteins. Disordered proteins are characterized by both extensive attraction and low energy cost from steric repulsion, contributing to easy observation of phase separation. Protein molecules form transient bonding networks in the droplet phase. The networks can be strengthened or disrupted by post-translational modifications, disease-associated mutations, and other macromolecular components such as RNA, leading to assembly and disassembly of MLOs.